KIR Variation in Iranians Combines High Haplotype and Allotype Diversity With an Abundance of Functional Inhibitory Receptors - Alicata, Claudia; Ashouri, Elham; Nemat-Gorgani, Neda; Guethlein, Lisbeth A.; Marin, Wesley M.; Tao, Sudan; Moretta, Lorenzo; Hollenbach, Jill A.; Trowsdale, John; Traherne, James A.; Ghaderi, Abbas; Parham, Peter; et al. (Frontiers in Immunology, 2020)
Natural killer (NK) cells are innate lymphocytes that eliminate infected and transformed cells. They discriminate healthy from diseased tissue through killer cell Ig-like receptor (KIR) recognition of HLA class I ligands. Directly impacting NK cell function, KIR polymorphism associates with infection control and multiple autoimmune and pregnancy syndromes. Here we analyse KIR diversity of 241 individuals representing five groups of Iranians. These five populations represent Baloch, Kur and Lur, together comprising 15% of the ethnically diverse Iranian population. We identified 159 KIR alleles, including 11 not previously characterized. We also identified 170 centromeric and 94 telomeric haplotypes, and 15 different KIR haplotypes carrying either a deletion or duplication encompassing one or more complete KIR genes. As expected, comparing our data with those representing major worldwide populations revealed the greatest similarity between Iranians and Europeans. Despite this similarity we observed higher frequencies of KIR3DL1*001 in Iran than any other population, and they have the highest frequency of HLA-B*51, a Bw4-containing allotype that acts as a strong educator of KIR3DL1*001+ NK cells. Compared to Europeans, the Iranians we studied also have a reduced frequency of 3DL1*004, which encodes an allotype that is not expressed at the NK cell surface. Concurrent with the resulting high frequency of strong viable interactions between inhibitory KIR and polymorphic HLA class I, the majority of KIR-A haplotypes characterized do not express a functional activating receptor. By contrast the most frequent KIR-B haplotype in Iran expresses only one functional inhibitory KIR and the maximum number of activating KIR. This first complete, high-resolution, characterization of the KIR locus of Iranians will form a valuable reference for future clinical and population studies.